Overweight as a biomarker for concomitant thyroid cancer in patients with Graves’ disease - Park, Joonseon; An, Solji; Bae, Ja Seong; Kim, Jeong Soo; Kim, Kwangsoon (Frontiers in Endocrinology, 2024)
The incidence of concomitant thyroid cancer in Graves' disease varies and Graves' disease can make the diagnosis and management of thyroid nodules more challenging. Since the majority of Graves' disease patients primarily received non-surgical treatment, identifying biomarkers for concomitant thyroid cancer in patients with Graves' disease may facilitate planning the surgery. The aim of this study is to identify the biomarkers for concurrent thyroid cancer in Graves' disease patients and evaluate the impact of being overweight on cancer risk. This retrospective cohort study analyzed 122 patients with Graves' disease who underwent thyroid surgery at Seoul St. Mary's Hospital (Seoul, Korea) from May 2010 to December 2022. Body mass index (BMI), preoperative thyroid function test, and thyroid stimulating hormone receptor antibody (TR-Ab) were measured. Overweight was defined as a BMI of 25 kg/m² or higher according to the World Health Organization (WHO). Most patients (88.5%) underwent total or near-total thyroidectomy. Multivariate analysis revealed that patients who were overweight had a higher risk of malignancy (Odds ratios, 3.108; 95% confidence intervals,; p = 0.021). Lower gland weight and lower preoperative TR-Ab were also biomarkers for malignancy in Graves' disease. Overweight patients with Graves' disease had a higher risk of thyroid cancer than non-overweight patients. A comprehensive assessment of overweight patients with Graves' disease is imperative for identifying concomitant thyroid cancer.